Is it justified to remove the intermediate risk group in the latest European guidelines for NSTEACS?. (14th October 2021) - Gonzalez Ferrero, T; Alvarez Alvarez, B; Ave, M T; Cordero, A; Sampedro, F G; Gonzalez Juanatey, J
Abstract: Background: Risk stratification in patients with non-ST elevation acute coronary syndrome (NSTEACS), becomes a priority after its diagnosis, due to the fact that it gives us information about prognosis and has crucial implications. The latest guidelines of European Society of Cardiology (ESC) suggest a new proposal of risk stratification dividing patients in three different groups: "low", "high" and "very high risk". Thus, they remove the intermediate risk group that defended the previous guidelines (2015). Purpose: Our aim was to identify an intermediate risk group following the recommendations of the previous guidelines about risk stratification. We believe that the risk stratification in four groups if more accurate that the latest proposed in 2020 in three groups, because the "intermediate risk group" has a different prognosis that the subgroup nowadays considered "low risk". Methods: We included a cohort of 7 597 patients with NSTEACS admitted in two different Cardiology departments between 2003 and 2017 with 4, 4±2, 7 mean years of follow-up. Subsequently, a classification of the patients in four different risk groups was made following the 2015 guidelines and events during follow-up was assigned in the next categories:first adverse major cardiovascular event (MACE), all-cause mortality and cardiovascular mortality. Results: Stratified analysis brought up that patients included in the intermediate risk group, had a different prognosis to the categories of "low" and "high risk" patients and we obtained the following results: Mean incidence rate for total mortality measured in cases per 100 person-year [confidence interval (CI 95%)] was 1.96; for "low risk" patients CI95% 1.30–2.95, "intermediate risk" 3.91; (CI95% 3.28–4.57), "high risk" 4.94; CI95% 4.87–5.21 and "very high risk" 8.74; CI95% 7.75- 9.85. Incidence rate for cardiovascular mortality for "low", "intermediate", "high" and "very high" was 1.02; (CI95% 0.58–1.18); 2.64 (CI95% 2.13–3.26); 3.32 (CI95% 3.11–3.55) and 6.71 (CI95% 4.84–7.69), respectively. Using Cox analysis, the "intermediate risk group" (refference), still achieved statistical significance. Results expressed in hazard ratio demonstrated that: Cardiovascular mortality, HR in "low", "high", "very high risk" groups were significantly different to "intermediate risk" group HR = 0.52; (CI95%, 0.33–0.81); HR = 1.05 (CI95%, 0.87–1.27); HR = 1.72; (CI95% 1.38–2.13), respectively. All-cause mortality, HR=0.40 (CI95%, 0.22–0.73); HR=1.02; (CI95% 0.81–1.28); HR=1.90 (CI95% 1.46- 2.46). MACE: HR=0.74 (CI95% 0.60–0.91); HR=0.72 (CI95% 0.65–0.80); HR=0.91 (CI95% 0.79–1.05). Conclusion: These findings suggest that the four categories proposal could have better ability for risk stratification in NSTEACS patients and make us doubt about the new three groups classification displayed in the current ESC guidelines, particularly the "intermediate risk" group exclusion that would be reassessed as "low risk". FUNDunding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): No funding sources.